A NATIONALCURRICULUM: COMPETITION, ADVANCES AND RETREATS - Aubusson, Pater (UPI Press, 2011)
This paper is an outcome of a study on National Science Curriculum (NSC) in Australia.This paper centres around the experts’ views on the scenarios of future science curriculum.The data were gathered through interviews with five leaders from different Australianstates. The data were analysed following the process of qualitative data analysis outlined byMcMillan and Schumacher (2006) involving selecting text extracts, identifying patterns,themes and key concepts, coding and categorisation, code testing against interpretationand constant comparison. The analysis is further checked by a research assistant. It will beshown that experts agree on the strengths and weaknesses of the curriculum. The resultsshow that there are two very different scenarios that seem possible. One emphasises stateindependence, standardisation, compliance and control. The other emphasises trust inteacher professionalism and knowledge exchange.Key words: National Science Curriculum, scenarios of future science curriculum